Sistem Penegakkan Hukum terhadap Tindak Pidana Pembakaran Hutan di Sumatera Selatan - Hasanal Mulkan; Serlika Aprita (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Law enforcement carried out by law enforcement officers in the criminal justice system is one of the efforts that can protect the public from various forms of criminal acts that violate the provisions of the regulations that have been made. In relation to law enforcement against perpetrators of clearing plantation land using the burning method, which often occurs in Indonesia, especially in the province of South Sumatra, the police have a very important role in enforcing the law so as to create fair law enforcement. Based on these reasons, law enforcement should indeed be on the perpetrators of clearing individual plantation lands that result in forest fires. Forests are natural resources that occupy a very strategic position because they contain abundant natural resources. Forest damage that causes the most severe impact is forest fires. In South Sumatra, every year forest fires are frequent. Law enforcement of the crime of forest burning is needed to reduce the occurrence of forest fires caused by human activities. to find out about law enforcement against the crime of forest burning that occurred in South Sumatra and the obstacles in law enforcement against the crime of forest burning in South Sumatra. The research specification used in this research is descriptive analytical, which describes all the symptoms and facts and analyzes the current problems related to law enforcement against the crime of forest burning. Law enforcement against the crime of forest burning in South Sumatra is running from the process of investigation, investigation, prosecution and court decisions has not been maximized. In enforcing the law against the crime of forest burning in South Sumatra, law enforcers encountered several obstacles, namely: the location of forest burning that was difficult to reach, the condition of peatlands that were easily burned, dry weather and strong winds that made fires grow and spread, and difficult to find evidence and witnesses.